COVID-19 and Cardiovascular Comorbidities - Müller-Wieland, Dirk; Marx, Nikolaus; Dreher, Michael; Fritzen, Katharina; Schnell, Oliver (Experimental and Clinical Endocrinology & Diabetes, 2020)
The emergence of a new coronavirus - severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - has resulted in a global pandemic. The associated coronavirus disease 2019 (COVID-19) has resulted in a high number of death worldwide. Observational studies and case reports have provided insights that older age and the presence of chronic diseases is frequently associated with a higher COVID-19 severity. These individuals also seem to have a higher risk of mortality due to COVID-19. In this review we provide insights into the impact chronic diseases associated with the cardiovascular system, such as obesity, diabetes mellitus, hypertension and cardiovascular disease might have on SARS-CoV-2 infection and COVID-19. Additionally we review recommendations and guidance’s of international scientific associations and discuss which key learnings might be of importance for the future.
Keywords: SARS-CoV-2; COVID-19; obesity; diabetes mellitus; hypertension, cardiovascular incidences; cardiovascular disease